Acupoint catgut embedding for chronic non-specific low back pain: A protocol of randomized controlled trial - Li, Xiaohui; Yin, Xiuju; Feng, Haiyan; Liao, Wangbin; Zhao, Jiayou; Su, Wu; Fan, Zhiyong; Wu, Shan (Frontiers in Neuroscience, 2023)
Chronic non-specific low back pain (CNLBP) is one of the leading causes of disability worldwide. Acupoint embedding (ACE) is widely used in China for the treatment of chronic non-specific low back pain, but there are no rigorous randomized controlled trials (RCTs) to confirm the effectiveness and safety of ACE for chronic non-specific low back pain. In this study, we design a single-center, single-blind, prospective RCT, with the aim of evaluating the efficacy and safety of ACE for CNLBP. 82 participants with CNLBP will be randomized in a 1:1 ratio into an ACE group and a sham ACE group. Participants will receive either ACE treatment or sham ACE treatment at once every 2 weeks, for an 8-week period, and followed by 6 months of follow-up. The primary outcome will be the change in visual analog scale (VAS) scores before and after treatment. Secondary outcomes will include the Oswestry Disability Index (ODI), the Roland Morris Disability Questionnaire (RMDQ) and the Short Form 36-Health Survey (SF-36). Adverse events that occur during the course of the trial will be recorded. Data will be analyzed according to a predefined statistical analysis plan. This study was approved by the medical ethics committee of Guangzhou Panyu Hospital of Chinese Medicine (202230). Written informed consent from patients is required. This trial is registered in the Chinese Clinical Trial Registry (ChiCTR2200059245). Trial results will be published in a peer-reviewed academic journal. Clinical trial registration https://www.chictr.org.cn, identifier ChiCTR2200059245.